Modern american drama Eugene O'Neil Long Day's journey into night - Lumet, Sidney; Landau, Ely.; Films for the humanities (Firm). (Princeton, N.J. Films for the Humanities, 1976)
A broading, devastating film based on Eugene O'Neil's most powerful and autobiographical play, about a day in the life of a family deteriorating because of drug addiction, alcoholism and imminent death.
VHS.
Narrator, Jose Quintero. Katherine Hepburn as Mary, Ralph Richardson as Tyrone, Jason Robards, as Jamie, Sean Stockwell as Edmund.
Keywords: O'Neill, Eugene, 1888-1953 -- Long days journey into night; Family problems -- Fiction; American drama -- 20th century